Re-evaluating serum angiotensin-converting enzyme in sarcoidosis - Zheng, Shi-yue; Du, Xin; Dong, Jian-zeng (Frontiers in Immunology, 2023)
Sarcoidosis is a systemic inflammatory disease of unknown etiology, which mainly affects the lungs and lymph nodes, as well as extrapulmonary organs. Its incidence, and prevalence rate, and disease course largely vary with regions and populations globally. The clinical manifestations of sarcoidosis depend on the affected organs and the degree of severity, and the diagnosis is mainly based on serum biomarkers, radiographic, magnetic resonance, or positron emission tomography imaging, and pathological biopsy. Noncaseating granulomas composing T cells, macrophages, epithelioid cells, and giant cells, were observed in a pathological biopsy, which was the characteristic pathological manifestation of sarcoidosis. Angiotensin-converting enzyme (ACE) was first found in the renin-angiotensin-aldosterone system. Its main function is to convert angiotensin I (Ang I) into Ang II, which plays an important role in regulating blood pressure. Also, an ACE insertion/deletion polymorphism exists in the human genome, which is involved in the occurrence and development of many diseases, including hypertension, heart failure, and sarcoidosis. The serum ACE level, most commonly used as a biomarker in diagnosing sarcoidosis, in patients with sarcoidosis increases. because of epithelioid cells and giant cells of sarcoid granuloma expressing ACE. Thus, it serves as the most commonly used biomarker in the diagnosis of sarcoidosis and also aids in analyzing its therapeutic effect and prognosis in patients with sarcoidosis.